Pulmonary artery occlusion by tuberculous mediastinal lymphadenopathy. Issue 3 (March 1997) - Drake, W M; Elkin, S L; al-Kutoubi, A; Mitchell, D M; Shaw, R J
Abstract : Two cases of tuberculous mediastinal lymphadenopathy are presented in which the clinical features mimicked those of pulmonary embolism, causing striking abnormalities on radionuclide scintigraphy. It is concluded that tuberculous mediastinal lymphadenopathy should be included in the differential diagnosis of reduced lung perfusion due to proximal pulmonary artery occlusion.